A genetic variant in CDKN2A/B gene is associated with the increased risk of breast cancer. Issue 1 (9th March 2017) - ShahidSales, Soodabeh; Mehramiz, Mehraneh; Ghasemi, Faezeh; Aledavood, Amir; Shamsi, Mehri; Hassanian, Seyed Mahdi; Ghayour‐Mobarhan, Majid; Avan, Amir
Abstract : Background: Breast cancer is among the leading cause of cancer‐related‐deaths in women, supporting the need for the identification of novel prognostic and predictive biomarkers. Recent studies have identified common genetic variants in a region on chromosome 9p21 associated with an increased risk of developing different cancers. Here, we explored the association of a genetic variant in CDKN2A/B, rs10811661, for the first time in 564 subjects with/without breast cancer. Method: Genotyping was performed using TaqMan real time PCR method. The associations of this genetic variant with breast cancer risk and pathological information of patients were assessed. Results: We observed that patients with breast cancer had a higher frequency of TT genotype ( P <.001) than control group, which was associated with advanced TNM classification ( P =.04) and larger tumor size ( P =.014), as detected by the recessive genetic inheritance model. Moreover, the logistic regression under recessive genetic model revealed that breast cancer patients with TT had higher risk of breast cancer, compared to CC/CT genotypes (eg, OR=4.9, 95% CI:1.9‐12, P= .001), after adjusted for potential confounders, age, BMI, and family history. Conclusion: We demonstrated that patients carrying the TT genotype for CDKN2A/B rs10811661 polymorphism had the increased risk of breast cancer susceptibility. However, further investigations are warranted in a larger and prospective setting to explore the value of this marker as a risk stratification marker in breast cancer.